BhbZIP60 from Resurrection Plant Boea hygrometrica Is an mRNA Splicing-Activated Endoplasmic Reticulum Stress Regulator Involved in Drought Tolerance - Wang, Bo; Du, Hong; Zhang, Zhennan; Xu, Wenzhong; Deng, Xin (Frontiers in Plant Science, 2017)
Adverse environmental conditions cause endoplasmic reticulum (ER) stress in plants. To mitigate ER stress damage, ER associated transcription factors and inositol-requiring enzyme-1 (IRE1)-mediated bZIP60 mRNA splicing are activated in plants. A drought-induced gene, encoding the ortholog of bZIP60, was identified in the resurrection plant Boea hygrometrica, termed BhbZIP60. In response to ER stress and dehydration, BhbZIP60 mRNA can be spliced to create a frame shift in the C terminus by the excision of 23b segment in a manner of its ortholog in other plants, thus translocating to the nucleus instead of the cytoplasm. The splicing-activated BhbZIP60 (BhbZIP60S) could function in the same way as its Arabidopsis ortholog by restoring the molecular phenotype of the mutant atbzip60. When overexpressed in Arabidopsis, BhbZIP60S provided transgenic plants with enhanced tolerance to drought, tunicamycin (TM) and mannitol stress with upregulation of the expressions of ER quality control (QC) genes (BiP2, BiP3, CNX1, and sPDI) and abscisic acid (ABA) responsive genes (RD29A, RAB18, and RD17). Furthermore, in the yeast one-hybrid system, BhbZIP60S was capable of interacting with ER stress responsive elements (ERSE and ERSE-II) that exist in the promoters of known ER-QC genes, but not binding to ABA responsive cis-elements (ABREs). Our results demonstrated that drought-induced BhbZIP60 may have a function in drought tolerance via the splicing-activated BhbZIP60S to mediate ER-QC by direct binding to the promoters of ER-QC genes. This study evidently demonstrates the involvement of ER-QC in the drought tolerance of Arabidopsis and the desiccation tolerance of the resurrection plant Boea hygrometrica.